An Ecological Approach to Children's Rights and Participation: Interrelationships and Correlates of Rights in Different Ecological Systems. (18th January 2013) - Ben‐Arieh, Asher; Attar‐Schwartz, Shalhevet
<x xml:space="preserve">Abstract</x> Current knowledge emphasizes either a developmental or a cultural/contextual theoretical framework for understanding children's approaches to the concepts of rights and participation. This study, carried out among 1, 753 Israeli adolescents (ages 15–17), uses a socioecological perspective instead to understand children's rights and participation. It examines adolescents' approaches to their rights and participation at 4 ecological levels—family, school, community, and the larger sociopolitical system—as well as a number of possible child, family, and societal correlates. It also looks at the interactions between some of these correlates. The findings show that different correlates have different links with various ecological circles. For example, girls reported higher levels of participation in the family and at school, but no significant differences were found between boys and girls in their participation in the community and at civic‐political levels. Israeli Palestinians reported higher levels of participation in their schools and at the civic‐political level but lower levels of participation in the family and the community compared with their Jewish counterparts. The significant interaction effect between nation and gender showed that, among Arab students, there were larger gaps between boys and girls in the different participation domains than there were among Jewish students. Furthermore, higher rates of participation in the family and lower rates of civic participation were found among students from single‐parent families. This study shows that employing an ecological framework to the efforts to understand children's approaches to rights and participation is a first step in the right direction for fostering children's rights and participation.